Uji Ketahanan 100 Jam Mesin Genset 27 KW Menggunakan Coco-Diesel - Fajar, Rizqon; Haryono, Ihwan; Kuddin, Misbah (MESIN, 2007)
Durability Test of Small Diesel Engine 27KW Using Coco-Diesel Today, government isconcern on using vegetable oil as alternative fuel which is environment friendly. Biofuel should betransformed to ester compound before used on diesel engines. It is caused that ester has similar physicalproperties comparing to the mineral oil (solar). This paper presents a durability test results on a dieselengine which used ester compoundfrom coconut diesel (coco methyl ester. The test was done for 100hours. The engine test used was a single cylinder Mitsubishi â¢with capacity 27 HP. The engine wascoupled by generator electricity. During durability test the generator was loaded by heaters 10 KW. Fuelconsumption, opacity, exhausts gas temperature andoil condition waschecked at 0, 50 and100hours.Keywords: coco-diesel, specificfuel consumption, opacity, viscosity